ECONOMIC AND PRACTICAL ASPECTS OF THE RETAIL PAYMENT SYSTEM OF COMMERCIAL BANKS (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the economic essence and theoretical foundations of the retail payment system in commercial banks. Retail payments, as a key component of financial transactions between individuals, businesses, and banks, play a crucial role in monetary circulation, financial stability, and improving the quality of banking services. The article explores core concepts, functions, and the role of the retail payment system in a market economy, along with theoretical models drawn from international experiences. The author also proposes recommendations for improving retail payment services within the banking system of Uzbekistan.